Source apportionment of polycyclic aromatic hydrocarbons in diverse environmental media using receptor and physico-chemical models - Sofowote, Uwayemi (My University, 2010)
This thesis focused on the interpretation of environmental data obtained from chemical analyses of complex and divergent environmental media. Environmental monitoring of pollutants yields large datasets which may be difficult to process using simplistic univariate approaches. Polycyclic aromatic hydrocarbons (PAH) are environmental organic contaminants that have important health implications and are ubiquitous in the environment. These compounds are regularly monitored in all environmental compartments but delineating their impacting sources from analytical data is usually challenging and thus not routinely attempted. The work contained in this thesis discusses how source information can be obtained by the application of (a) qualitative relationships, (b) physico-chemical models dealing with phase change and partitioning, as well as (c) receptor models using factor analysis to P AH data collected in samples from the atmosphere and in suspended sediments. There are unique concepts and new applications embodied in this thesis. They include: (a) The development and definition of a new diagnostic relationship that discriminates between industrial and urban sources of P AH, (b) the integration of qualitative diagnostic correlations with measured concentration data to improve the diagnostic potential of these simple non-multivariate relationships, (c) the integration of local meteorological data with receptor modeling using factor analysis to explicitly identify impacting PAH source regions, and finally (d) the first known instance of the use of a hybridized receptor modeling methodology to explicitly identify, quantify and spatially map the potential source regions of P AH on a hemispheric scale. An additional effect of the work contained herein is that it shows how much information which could be useful to environmentalists and policy-makers in designing effective abatement and control strategies if available is usually left un-extracted from environmental monitoring activities.
Keywords: polycyclic aromatic; hydrocarbons; receptor; physico-chemical; environmental media